Paediatric advanced life support : a Practical Guide for Nurses - Jevon, Philip (Chichester, West Sussex, UK : John Wiley & Sons, 2012)
In the event of a paediatric cardiac arrest, it is essential to be able to respond rapidly, providing safe and effective care. The second edition of this successful text provides you with a practical and systematic guide to the rapid assessment and delivery of appropriate resuscitation to infants and children. Conforms to current European Resuscitation Council GuidelinesBased on up-to-date research and evidence-based practice protocolsSynoptic approach enables rapid delivery of effective treatmentWritten by experts in the field of both resuscitation and paediatrics. Paediatric Advanced Life Supp.
An overview of paediatric advanced life support -- Resuscitation equipment for paediatric resuscitation -- Recognition of the seriously ill child -- Paediatric basic life support -- Airway management and ventilation -- ECG recognition and management of cardiac arrhythmias -- Defibrillation and electrical cardioversion -- Paediatric advanced life support -- Management of anaphylaxis -- Resuscitation in special situations -- Post-resuscitation care -- Bereavement -- Records, record-keeping and audit -- Legal and ethical issues -- Resuscitation training -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Pediatric emergencies; Pediatric intensive care; Life support systems (Critical care); Child; Critical Care -- methods; Critical Illness -- nursing; Infant; Life Support Care -- methods; MEDICAL -- Critical Care; MEDICAL -- Nursing -- Critical & Intensive Care; Life support systems (Critical care); Pediatric emergencies; Pediatric intensive care; Electronic books